Language input, learning environment, and motivation of a successful EFL learner - Arif Nugroho; M. Rizal Akbar Zamzami; Nur Farah Ukhrowiyah (Journal on English as a Foreign Language, 2020)
The present study involved one EFL learner who was regarded as successful, not only of understanding second language acquisition theories but also of demonstrating exceptional language skills thus far. An in-depth semi-structured interview was administered with three key objectives